Management of Strengthening Character Education of Students during the COVID-19 Period in Elementary School Creative Schools: Manajemen Penguatan Pendidikan Karakter Siswa Masa COVID-19 di Sekolah Kreatif Sekolah Dasar - Masulah, Uun; Wahyuni, Akhtim (Universitas Muhammadiyah Sidoarjo, 2023)
The management of character education strengthening is a leadership effort in planning, organizing, monitoring and evaluating student’s strengthening character, specifically during the pandemic Covid-19. The purpose of this thesis to analyze educational planning, organization, implementation and give an evaluation of the students strengthening character education during pandemic Covid-19 at Creative School of Muhammadiyah 2 elementary school 2 tulangan sidoarjo. This research used qualitative approaches with the subjects of the research are taken from the Principal, Vice-Principals, extracurricular teachers, Qur’an teachers, teachers, and Parents. This research was taken at Creative School of Muhamadiyah 2 Elementary School Tulangan Sidoarjo. Data collection techniques used in this research was interviews and observations. The data analysis technique in this research include data, reduction, data presentation and conclusion or verification. The result of this research indicate that: (1) The management planning of character education strengthening for students during the Pandemic Covid-19 at the Creative School of Muhammadiyah 2 Tulangan has implemented all the stages include planning and strategy, program socialization, administration and the learning media. (2) Organizing the students character of education strengthening during the pandemic Covid-19 at the Creative School of Muhammadiyah 2 Tulangan has been implemented by all of the stake holder to grow and achieve good habit easily. (3) The implementation of students character during the pandemic Covid-19 at the Creative School of Muhammadiyah 2 elementary school Tulangan Sidoarjo can be run quite well and effectively which is divided into 4 activities, those are: daily activities, spontaneous activities, programmed activities and exemplary activities. (4) The supervisions of students character strengthening during the pandemic Covid-19 at the Creative School of Muhammadiyah 2 elementary school Tulangan Sidoarjo has been implemented by the Principal and all of the stake holders to find out how the students character strengthening has been applied. (5) Monitoring and evaluation the management of students character education during the pandemic Covid-19 at the Creative School of Muhammadiyah 2 elementary school Tulangan Sidoarjo performed by the Principal, Vice Principal to communicate the students progress to the parents. (6) Students character during the pandemic Coid-19 at the Creative School of Muhammadiyah 2 elementary school Tulangan Sidoarjo, specially the religious character has become habit among the students On the other side, most of the good character of students have been lost and decreased